Abnormal outer and inner retina in a mouse model of Huntington’s disease with age - Yang, Dashuang; Huang, Chunhui; Guo, Xuemeng; Li, Yintian; Wu, Jiaxi; Zhang, Zaijun; Yan, Sen; Xu, Ying (Frontiers in Aging Neuroscience, 2024)
Huntington's disease (HD) is a progressive neurodegenerative disorder characterized by motor dysfunction and cognitive decline. While retinal abnormalities have been documented in some HD patients and animal models, the nature of these abnormalities-specifically whether they originate in the inner or outer retina-remains unclear, particularly regarding their progression with age. This study investigates the retinal structure and function in HD transgenic mice (R6/1) compared to C57BL/6J control mice at 2, 4, and 6 months of age, encompassing both pre-symptomatic and symptomatic stages of HD. Pathological assessments of the striatum and evaluations of motor function confirmed significant HD-related alterations in R6/1 mice at 6 months. Visual function was subsequently analyzed, accompanied by immunofluorescent staining of retinal and optic nerve tissues over time. Our findings revealed that R6/1 mice exhibited pronounced HD symptoms at 6 months, characterized by neuronal loss in the striatum and impaired locomotor abilities. Functionally, visual acuity declined at 6 months, while retinal light responses began to deteriorate by 4 months. Structurally, R6/1 mice demonstrated a global reduction in cone opsin expression as early as 2 months, with a decrease in rhodopsin levels at 4 months, alongside a thinner retinal structure compared to controls. Notably, rod bipolar cell populations were diminished at 6 months, exhibiting shorter dendritic branches and reduced synaptic connections with photoreceptors in the outer retina.Additionally, ganglion cell numbers in the inner retina decreased at 6 months, accompanied by aberrant neural fibers in the optic nerve. Microglial activation was evident at 4 months, while astrocytic activation was observed at 6 months. Aggregates of mutant huntingtin (mHTT) were first detected in the ganglion cell layer and optic nerve at 2 months, subsequently disseminating throughout all retinal layers with advancing age. These results indicate that retinal pathology in R6/1 mice manifests earlier in the outer retina than in the inner retina, which does not align with the progression of mHTT aggregation. Consequently, the R6/1 mouse retina may serve as a more effective model for elucidating the mechanisms underlying HD and evaluating potential therapeutic strategies, rather than functioning as an early diagnostic tool for the disease.